2020
DOI: 10.1029/2019gl085800
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology of Saturn's Aurorae Observed During the Cassini Grand Finale

Abstract: Cassini's mission exploring the Saturn system ended with the Grand Finale, a series of orbits bringing the spacecraft closer to the planet than ever before and providing unique opportunities for observations of the ultraviolet aurorae. This study presents a selection of high‐resolution imagery showing the aurorae's small‐scale structure in unprecedented detail. We find the main arc to vary between a smooth and a rippled structure, likely indicating quiet and disturbed magnetospheric conditions, respectively. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In addition to the main oval, Saturn's aurora also has a dimmer emission equatorward of the main oval called the outer emission. The outer emission boundaries map to a distance of~6-7 R S in the magnetic equator plane (Bader et al, 2020) corresponding to a striking plasma boundary at 7 R S as identified in Schippers et al (2008). Inward of that boundary, the electron pitch angle distributions are trapped and have pancake or butterfly distributions, whereas outward of that boundary, the pitch angle distributions are bidirectional.…”
Section: 1029/2019ja027693mentioning
confidence: 97%
“…In addition to the main oval, Saturn's aurora also has a dimmer emission equatorward of the main oval called the outer emission. The outer emission boundaries map to a distance of~6-7 R S in the magnetic equator plane (Bader et al, 2020) corresponding to a striking plasma boundary at 7 R S as identified in Schippers et al (2008). Inward of that boundary, the electron pitch angle distributions are trapped and have pancake or butterfly distributions, whereas outward of that boundary, the pitch angle distributions are bidirectional.…”
Section: 1029/2019ja027693mentioning
confidence: 97%
“…Pulsations in the ultraviolet (UV) auroral emissions have further been linked with magnetodisc reconnection and are observed to preferentially occur at dusk with patchy, diffuse signatures (Bader et al, 2019(Bader et al, , 2020. These phenomena highlight the quieter dawn magnetodisc that maps to the aurora along field-aligned currents compared to the active and more variable dusk magnetodisc and cushion that generate these structures.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 3b and 3c also suggests a tendency for the currents in the southern hemisphere to be a little larger than those in the northern hemisphere irrespective of season. This could be a consequence of the weaker ionospheric magnetic fields in the southern hemisphere compared with the northern hemisphere, which may act both to somewhat enhance weak diffusion particle precipitation into the southern hemisphere compared with the northern hemisphere as reported by Bader et al (2020), as well as to increase the conductivity (the mobility) of the ionization produced.…”
Section: Comparison Ofmentioning
confidence: 90%